2022
DOI: 10.3390/biomedicines10051173
|View full text |Cite
|
Sign up to set email alerts
|

Lung Inflammation Predictors in Combined Immune Checkpoint-Inhibitor and Radiation Therapy—Proof-of-Concept Animal Study

Abstract: Purpose: Combined radiotherapy (RT) and immune checkpoint-inhibitor (ICI) therapy can act synergistically to enhance tumor response beyond what either treatment can achieve alone. Alongside the revolutionary impact of ICIs on cancer therapy, life-threatening potential side effects, such as checkpoint-inhibitor-induced (CIP) pneumonitis, remain underreported and unpredictable. In this preclinical study, we hypothesized that routinely collected data such as imaging, blood counts, and blood cytokine levels can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The application of radiomics to tumor immune microenvironment (TIME) dynamics is a further development of the habitat concept. Our prior preclinical work demonstrated that radiomics of pretreatment MR and CT imaging can predict lymphoid and myeloid infiltration of tissue in regions of interest ( 34 ). In that study and the current one, the texture feature “ CT average gray ” emerged as predictive of treatment effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of radiomics to tumor immune microenvironment (TIME) dynamics is a further development of the habitat concept. Our prior preclinical work demonstrated that radiomics of pretreatment MR and CT imaging can predict lymphoid and myeloid infiltration of tissue in regions of interest ( 34 ). In that study and the current one, the texture feature “ CT average gray ” emerged as predictive of treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Radiomic analysis assumes that patterns (known as “ features ” ) below the threshold of visual detection are present within medical imaging and reflect underlying pathophysiology; converts medical imaging into mineable data and extracts clinically relevant features to improve cancer diagnosis, prognosis, prediction, and assessment of treatment response; and has augmented predictive models in diverse cancer types ( 32 , 33 ) using conventional imaging studies such as computed tomography (CT) and magnetic resonance imaging (MRI). Advanced radiomics can quantify and analyze subregions within tumors which reflect differences in underlying tumor pathophysiology ( 31 ), such as lymphoid infiltration within highlighted areas ( 34 ). CT radiomics are of particular interest as these studies are commonly obtained for patients with aNSCLC, and CT texture features from pretreatment imaging have been incorporated in biomarker studies predicting for response to ICI ( 35 , 36 ).…”
Section: Introductionmentioning
confidence: 99%
“…The regions containing inflammatory cells were outlined to obtain the value of the area occupied in terms of pixels, and this value was then normalized to the total area of the examined sample, also expressed in pixels (Figure 2C). This procedure allowed obtaining a percentage value that could be compared across different samples, as it is relative rather than absolute and independent of the size of the sample itself 39 . Collagen stained by picrosirius red staining, was quantified through color deconvolution.…”
Section: Methodsmentioning
confidence: 99%
“…This procedure allowed obtaining a percentage value that could be compared across different samples, as it is relative rather than absolute and independent of the size of the sample itself. 39 Collagen stained by picrosirius red staining, was quantified through color deconvolution. Collagen quantification was expressed as a proportion of collagen-occupied surface and the total sample surface.…”
Section: Histological Assessmentmentioning
confidence: 99%
“…Mice were bilaterally imaged with CT and MRI after subcutaneous tumor formation and blood collection, and then treated with RT of the right abdominal tumor only (3*8Gy) followed by intraperitoneal injection of PD-1 inhibitors. They found that 3 CT radiomic features (mean grayscale, histogram kurtosis and co-occurrence matrix entropy) and 1 MRI feature (histogram kurtosis) together with baseline neutrophil-to-lymphocyte ratio (NLR) and granulocyte-macrophage colony-stimulating factor (GMSF) levels were positively correlated with CD45 infiltration ( 22 ). However, it is important to note that this model only assessed the CD45 infiltration levels to indicate the occurrence of pneumonia is not sufficiently reasonable and could not distinguish between RIP and CIP.…”
Section: Prediction Of Cip By Ct Radiomicsmentioning
confidence: 99%